Les pièces de monnaies de l’empereur Nerva provenant de la collection du Musée Archéologique et Ethnographique de Łódź: The Coins of the Emperor Nerva From the Collection of the Archaeological and Etnographical Museum In Łódź - Jarzęcki, Krzysztof (Acta Archaeologica Lodziensia, 2019)
The paper is dedicated to the 15 coins of the emperor Nerva from the collection of the Archaeological and Etnographical Museum in Łódź: 7 denarii, 3 sestertii, 1 dupondius and 4 ases. All the coins were purchased. Author evaluates them popularity and weight parameters based on a comparison to finds, especially hoards and informations from the auction houses.